2021
DOI: 10.3389/fgene.2021.699920
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Seasonal Heat Stress on Transcriptomic Profiles and Global DNA Methylation of Bovine Oocytes

Abstract: Heat stress affects oocyte developmental competence and is a major cause of reduced fertility in heat stressed cattle. Negative effects of heat stress on the oocyte have been observed at morphological, biochemical and developmental levels. However, the mechanisms by which heat stress affects the oocyte at the transcriptional and epigenetic levels remain to be further elucidated. Here we aimed to investigate the effect of heat stress on oocyte quality, transcriptomic profiles and DNA methylation of oocytes coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…Sigdel et al ( 2019 ) reported HSF1, MAPK8IP1 , and CDKN1B as genes responsible for thermotolerance in dairy cattle. Moreover, Diaz et al ( 2021 ) identified five genes: E2F8, GATAD2B, BHLHE41, FBXO44 , and RAB39B which were significantly associated with HS. In this study, it was found that the gene RAB39B was significantly associated with three phenotypes which included rectal temperature, drooling, and respiratory scores.…”
Section: Resultsmentioning
confidence: 99%
“…Sigdel et al ( 2019 ) reported HSF1, MAPK8IP1 , and CDKN1B as genes responsible for thermotolerance in dairy cattle. Moreover, Diaz et al ( 2021 ) identified five genes: E2F8, GATAD2B, BHLHE41, FBXO44 , and RAB39B which were significantly associated with HS. In this study, it was found that the gene RAB39B was significantly associated with three phenotypes which included rectal temperature, drooling, and respiratory scores.…”
Section: Resultsmentioning
confidence: 99%
“…Sigdel (Sigdel et al, 2019) reported HSF1, MAPK8IP1 , and CDKN1B as genes responsible for thermotolerance in dairy cattle. Moreover, Diaz (Diaz et al, 2021) identified five genes: E2F8, GATAD2B, BHLHE41, FBXO44 , and RAB39B which were significantly associated with HS. In this study, it was found that the gene RAB39B was significantly associated with three phenotypes which included rectal temperature, drooling, and respiratory scores.…”
Section: Resultsmentioning
confidence: 99%
“…Embryos used for in vitro fertilization with oocytes obtained from sexually immature heifers show lower cleavage and blastocyst rates compared with those obtained from mature cows (Presicce et al, 1997;Rizos et al, 2005). Moreover, the quality of oocytes deteriorates in the summer (Baruselli et al, 2020;Diaz et al, 2021). Therefore, the combination of sperm sex sorting, female immaturity, and heat stress might interdependently decrease the conception rates of nulliparous cows using sexed semen in warmer months, suggesting that insemination using sexed semen in nulliparous cows should be avoided in warmer months.…”
Section: Discussionmentioning
confidence: 99%